Salud mental en estudiantes de posgrado en Brasil: relaciones con sobrecarga de trabajo y éxito en la carrera - Pinzón, Juanita Hincapié (2019)
The aim of this study was to investigate the relationship between work overload, objective and subjective perception of career success, work-family / family-work enrichment, difficulties in the work context and the appearance of symptoms of depression, anxiety and stress in graduate students. For that, three studies were carried out. The first was a systematic review that aimed to examine in the literature the variables related to mental health in graduate students and professors. Consequently, the models in health to which these analyzes are assigned and the proposals around them, in search of the theoretical-practical consolidation of a comprehensive vision of health, greater academic contributions and intervention proposals that encourage, strengthen and improve the health mechanisms. The search for studies covered articles published in English, Portuguese and Spanish, with a temporary cut from 2013 to April 2018, belonging to the graduate area. What resulted in 24 items for the final sample. The major contributions and findings of the analyzed articles say regarding the protective factors and risk predictors that contribute to the psychic suffering. In addition, variables of gender, origin, social, cultural and contextual differences that influence well-being, academic performance, meaning of work and career decisions in the educational area. The second study aimed to present data related to mental health of graduate students in Brazil. From a transversal and quantitative section, a sample of 1619 masters and doctoral students was collected. They answered an online survey that collected data about the profile, and the presence of symptoms of depression, stress, anxiety; the perception of career success, work overload, work-family / family-work enrichment and difficulties in the work context. The data were subjected to descriptive analysis of mean, frequency and comparison between groups. The main results indicate that students suffer from high levels of depression, anxiety and stress; and a considerable percentage claimed to have attempted suicide after entering graduate school. In particular, the prevalence of symptoms in Humanities students was found. It is concluded that the perceived work overload and the difficulties in the work context may be interfering and generating conflicts with the family and, in turn, diminishing the perception of success in the career. In addition, although the graduate students fulfill their academic, work and apparently see objective success in their careers, they present ideas and suicidal intention, difficult to perceive at first sight and even with instruments of high reliability. Finally, the third study investigated the perception of postgraduate students about their mental health and various factors of their work, by means of a transversal and quantitative cut. Aspects of the difficulties present in the work context, overload of work, perception of success in the career, work-family / family-work enrichment, and symptoms of depression, stress and anxiety were evaluated. The sample was composed of 1619 master's and doctoral students (M = 29.7 years, DP = 5.8), who answered a socio-demographic questionnaire and tools to evaluate the constructs studied. Descriptive analyzes, hierarchical regression (stepwise method) and network analysis were carried out. It was verified that the CAPES grade of the course and having a scholarship are related to the work overload, in addition to the difficulties in the work context, which affect the mental health of the students. The symptoms of anxiety, stress and depression were inversely proportional to the family-work enrichment and the perception of success in the career. The most central variable was having children. Others that were related to the system in a positive sense were work-family enrichment and subjective success, which together show the importance of making interventions that promote the meaning and construction of the subject's life. It reinforces the need to invest in protective and preventive measures for the mental health of academics who work to generate knowledge, promoting, among other factors, a healthy working environment and conditions.